Public Perception and the Effectiveness of the Safe City Sargodha Project: Implications for Traffic Regulation, Crime Detection, and Urban Safety - Muhammad Noor Ul Mudassir; Malik Kaleem Ullah; Zain Ullah (Social Science Review Archives, 2025)
Over the past few years, there has been a strong introduction of surveillance-led urban management in the developing countries in an effort to counter issues concerning traffic control and prevention of crimes. In this study, the researcher explores the community feeling towards the effectiveness of Sargodha Safe City project, specifically traffic control, crime prevention and detection, security perception and general community sentiment. The quantitative cross sectional research design was used and information was collected on 200 residents of Sargodha through a structured questionnaire based on five-point Likert scale. The obtained data was processed with the help of descriptive statistics and simple linear regression. The results show that the positive attitude of the population has statistically significant effect to the opinion of efficient traffic management and crime detection. On the other hand, the effect of the Safe City Project on the feelings of safety of people seemed to be insignificant, and the correlation between this project and the views of the general population was not statistically significant. The paper concludes that surveillance technologies can improve the results of regulatory and enforcement; however, their effectiveness in the establishment of perceived safety depends on the views of larger institutions, transparency, and a sense of community participation. The implications of these findings on policy in terms of the legal aspects of surveillance in city security efforts in the third world countries are huge.